Learning from the lived experiences of Lakota, Navajo, Chicana, Latina, and Hispanic women ranchers across Turtle Island through pláticas - Gloria-Martinez, Ariana Isabel, author; David-Chavez, Dominique, advisor; Ganguli, Amy, committee member; Fernández-Giménez, María, committee member; Archibeque-Engle, Shannon, committee member (Colorado State University. Libraries, 2026)
Rangeland social science research has historically relied on quantitative, survey-based methods that obscure the socio-political and historical realities that shape rancher decision-making, including how conservation innovations are evaluated, adapted, or resisted. These approaches, often seemingly apolitical, have historically and overwhelmingly focused on white, Euro-American male ranchers, and to a lesser extent, white, Euro-American women ranchers, while almost entirely excluding the experiences, perspectives, and contributions of Indigenous, Black, and ranchers of color, especially women. By lacking intersectional feminist analysis, such research has reinforced harmful narratives that invisibilize systemic oppression and erase settler-colonial history and its ongoing legacy. The narratives promoted by existing research, mask the attempted intergenerational dispossession of ancestral homelands, cultural practices, and lifeways, along with the herstorical leadership, contributions and knowledge systems of Indigenous, Black and other women of color ranching communities. In doing so, this body of work has upheld settler-colonial and capitalist frameworks of land and livestock management, narrowing the field of rangeland science and limiting the possibilities for more just and inclusive futures. This thesis provides a timely intervention, grounded in Chicana feminist and Indigenous feminist theory as methodology and praxis. I conducted ten semi-structured life herstory pláticas with Lakota, Navajo, Latina, Chicana, and Hispana women ranchers across the western bioregion of Turtle Island. Their stories illuminate ranching as a feminist-liberatory practice rooted in responsibility to ancestors, community, land, animals, and future generations. Their primary goals and motivations to continue ranching included strong ties to their ancestral homelands, responsibility for caring for the land and all her kin as Mother Earth cares for them, and a need to pass their teachings and way of life on to future generations. The women identified challenges such as prolonged drought, climate change, financial strains intensified by Covid-19, volatile livestock markets, and barriers to processing their own meat and keeping it in their communities. Successes included producing healthy animals and high-quality meat on healthy rangelands, keeping land in the family and serving as role models within their communities. These findings reframe ranching as a cultural, ecological, and political practice rather than solely an economic activity. The development and adoption of innovations serve to learn from following a community-led, ground-up model that begins with the standpoints of ranchers, their lived experiences, goals, challenges, successes and adaptive management strategies, so that innovations are co-developed to be practical and relevant to their specific needs. A deeper understanding and centering of the lived experiences of Indigenous rancher, Black rancher, and ranchers of color, especially women ranchers of those communities, who remain largely excluded from this field can inform more equitable and effective policy, outreach, and conservation tools. This thesis affirms the importance of intersectional, Indigenous, and Chicana feminist analysis, representation, and relational accountability in rangeland science. It also calls for systemic transformation so that the field more accurately reflects Indigenous women ranchers as original and longstanding stewards of these lands, and how they, along with Black women ranchers and other women of color ranchers, endure as innovators, leaders, and caretakers of land-based presents and futures, despite being overwhelmingly ignored or excluded in rangeland science research. Furthermore, this work fills a critical gap in representation important to younger generations in this field to get to see themselves, their communities' values, their herstories, their leadership and contributions fully reflected across journals, panels, conference presentations, classrooms, and other academic and professional spaces in this field.
Keywords: decolonizing methodologies; Indigenous women; traditional ecological knowledge; Indigenous knowledge systems; community-based participatory research; rangeland stewardship